The conflict between property rights and environmental rights under constitutional law - Stoffel, Christian Werner (Department of Public Law, 2023)
'The Lord God took the man and put him in the Garden of Eden to work it and take care of it.'(Gen 2, 15) Ever since that time, mankind has the obligation to deal with his environment with special regard to how to use and take care of it. At today's time the concern for a clean environment is increasing and can - in its global application - be only compared to the increasing struggle for the international protection of human rights after the Second World War. The protection and the management of the environment has become one of the central questions on a global level and the survival of mankind can only be guaranteed if the international community - as well as the single states - learns to deal with the questions that result from increasing industrialisation and development. On an international level the ratification of international conventions and treaties is an important tool to put international standards into effect. On the national or municipal level the inclusion of an environmental clause in the state constitution has become an interesting tool to rule and direct national environmental legislation and its implementation. Under South African constitutional law not only the Constitution of South Africa Act 200 of 1993 but also the Constitution of South Africa Act 108 of 1996 contains an 'environmental clause' in its Bill of Rights. The inclusion of an 'environmental clause' in a national constitution is a relatively new tendency and has over the years been followed by many states that recognized that the protection of the environment demands action on a constitutional level. Another right that is traditionally incorporated in a state's Bill of Rights is the 'right to property' or - generally speaking - a 'property clause' that protects private property. The interest for private property is as closely interwoven with human interests as dealing with the environment - though its protection has much earlier been recognized as being necessary. However, in modern times it became clear that the protection and the management of the environments demands limitations of existing property rights. Since the Bill of Rights of the South African Interim Constitution and of the South African Constitution contains both clauses, this paper shows where the rights can conflict and how conflicts should be solved with special regard to land-related questions.